The Effect Of Incentives On Employee Performance In The Public Works And Spatial Planning Office Of Asahan Regency - Shandy Evanda Santayana; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the effect of incentives on employee performance at the Public Works and Spatial Planning Office of Asahan Regency. Incentives are considered as factors that can increase employee motivation and performance in achieving predetermined targets and standards. This type of research is quantitative research with a casual associative approach, involving 145 employees as research samples using saturated sampling techniques. Data were collected through questionnaires, distributed to all employees and analyzed using SPSS version 25.0. The results of the linear regression analysis showed that incentives have a significant positive effect on employee performance, with a regression coefficient of 1.480 and a significance value of 0.000 (p <0.05). The coefficient of determination (R²) of 0.762 indicates that incentives contribute 76.2% to improving employee performance, while the rest is influenced by other factors. Based on the hypothesis test, there is a significant positive effect between incentives and employee performance, as indicated by the t-count value of 21.387 which is greater than the t-table of 1.97669. This study concludes that incentives play an important role in improving employee performance at the Public Works and Spatial Planning Service of Asahan Regency, and it is recommended that organizations design more strategic incentives that are in accordance with employee needs to achieve more optimal results.